Contribution of Neuroepigenetics to Huntington’s Disease - Francelle, Laetitia; Lotz, Caroline; Outeiro, Tiago; Brouillet, Emmanuel; Merienne, Karine (Frontiers in Human Neuroscience, 2017)
Unbalanced epigenetic regulation is thought to contribute to the progression of several neurodegenerative diseases, including Huntington’s disease (HD), a genetic disorder considered as a paradigm of epigenetic dysregulation. In this review, we attempt to address open questions regarding the role of epigenetic changes in HD, in the light of recent advances in neuroepigenetics. We particularly discuss studies using genome-wide scale approaches that provide insights into the relationship between epigenetic regulations, gene expression and neuronal activity in normal and diseased neurons, including HD neurons. We propose that cell-type specific techniques and 3D-based methods will advance knowledge of epigenome in the context of brain region vulnerability in neurodegenerative diseases. A better understanding of the mechanisms underlying epigenetic changes and of their consequences in neurodegenerative diseases is required to design therapeutic strategies more effective than current strategies based on HDAC inhibitors. Researches in HD may play a driving role in this process.